Drylands: the opportunities you never imagined - CGIAR Research Program on Dryland Systems; International Center for Tropical Agriculture (2015)
Discover the opportunities that drylands hold to help tackle some of the world's most pressing challenges in this short animation created by the International Center for Tropical Agriculture (CIAT) and the CGIAR Research Program on Dryland Systems. Art and Motion: Nathalia Mejía https://www.behance.net/nathaliamejia... Music: Dryland by © Davide De Gregorio http://www.ddgproject.com / BMI Work No: 020554963